2019
DOI: 10.1186/s12940-018-0435-5
|View full text |Cite
|
Sign up to set email alerts
|

The evidence of human exposure to glyphosate: a review

Abstract: BackgroundDespite the growing and widespread use of glyphosate, a broad-spectrum herbicide and desiccant, very few studies have evaluated the extent and amount of human exposure.ObjectiveWe review documented levels of human exposure among workers in occupational settings and the general population.MethodsWe conducted a review of scientific publications on glyphosate levels in humans; 19 studies were identified, of which five investigated occupational exposure to glyphosate, 11 documented the exposure in genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
153
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(161 citation statements)
references
References 27 publications
3
153
0
5
Order By: Relevance
“…During occupational exposure, GLY enters the human circulation mainly through the respiratory tract, but only ≤2% of the sediment on the skin enters the internal circulation [33]. A review by Gillezeau et al [34] documented levels of human exposure to GLY among workers in occupational settings and the general population. Urinary GLY concentrations were assessed in 423 people who were occupationally and para-occupationally exposed from eight studied reports, as well as 3298 general subjects' biological samples from 14 research reports.…”
Section: Discussionmentioning
confidence: 99%
“…During occupational exposure, GLY enters the human circulation mainly through the respiratory tract, but only ≤2% of the sediment on the skin enters the internal circulation [33]. A review by Gillezeau et al [34] documented levels of human exposure to GLY among workers in occupational settings and the general population. Urinary GLY concentrations were assessed in 423 people who were occupationally and para-occupationally exposed from eight studied reports, as well as 3298 general subjects' biological samples from 14 research reports.…”
Section: Discussionmentioning
confidence: 99%
“…Glyphosate and its metabolite AMPA can be found in soils, water, plants, food, and animals (Alferness and Iwata 2002;Caloni et al 2016;El-Gendy et al 2018). Glyphosate is detected in human urine, blood, and maternal milk, with urinary levels of 0.26-73.5 lg/L in exposed workers and 0.16-7.6 lg/L in the general population (Acquavella et al 2004;Gillezeau et al 2019). Glyphosate most likely enters the body via the dermal, oral and pulmonary routes (Martinez et al 1990;Williams et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Valid data on the extent of human exposure to glyphosate in the general population are essential for scientifically substantiated risk assessments. Human exposure can be monitored by measuring the urinary levels of glyphosate and AMPA, although the available data sets are very limited in number (Gillezeau et al 2019). EFSA reported that published glyphosate levels in human urine samples resulting from dietary intake of glyphosate represented 0.1-0.66% of the ADI, while the maximum levels of AMPA in human urine samples were estimated to remain below 0.1% of the ADI (EFSA 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum values were 2.80 µg glyphosate/L and 1.88 µg AMPA/L, both of them measured in samples from 2013. With regard to studies from additional countries dealing with human exposure to glyphosate, we refer to the current review of Gillezeau et al (2019). This review listed three studies investigating the association between glyphosate/AMPA exposure and food consumption or dietary pattern in the general population (no occupational exposure) (Knudsen et al 2017;McGuire et al 2016;Parvez et al 2018).…”
Section: Introductionmentioning
confidence: 99%